Lines of Credit and Relationship Lending in Small Firm Finance - Allen N. Berger; Gregory E. Udell (Levy Economics Institute of Bard College, 1994)
This paper examines the role of_.relationship..lending.using a data set on small firm finance. We specifically examine price and nonprice terms of commercial bank lines of credit (L/C) extended to small firms. Our focus on bank L/Cs allows us to examine a type of loan contract where the bank-borrower relationship is likely to be an important mechanism for solving asymmetric information problems associated with financing small enterprises. We find that borrowers with longer banking relationships tend to pay lower interest rates and are less likely to pledge collateral. These results are consistent with theoretical arguments that relationship lending generates valuable information about borrower quality.
Keywords: 330